Feasibility study of brown mustard (Brassica juncea (l.) Czern) plant as a raw material for manufacturing of particle board (International Journal of Scientific Research and Management (IJSRM), 2022)
Particle board is mostly used as alternative to wood at present age to reduce the pressure on solid wood. Different raw materials, mostly woody and non woody materials are used as wood particle and various resins are used as binder. Now-a-days, vegetable wastages are also utilized. This study was conducted to compare the feasibility of using Brown Mustard (Brassica juncea (L.) Czern) plant wastage for manufacturing of particleboard. The physical and mechanical properties of brown mustard board were tested to access its quality. The particle board made from brown mustard waste presents good physical and mechanical properties. It was found that the density of brown mustard particleboard was 0.836 gm/cm3, moisture content was 6.95%, water absorption was 37.69 %, thickness swelling was 14.58 %, linear expansion was 0.96%, Modulus of Rupture was 26.39 N/mm2 and Modulus of Elasticity was 2795.64 N/mm2. The physical and the mechanical properties of particle board of brown mustard waste were compared with the properties of market particle boards. Therefore, it can be concluded that brown mustard wastage can be used as alternative raw material for particleboard manufacturing.